Renal cell carcinoma of the native kidney in renal transplant recipients: case report and literature review - Tao, Yi; Wang, Jun; Peng, Yulan; Zhou, Jiaojiao (Frontiers in Oncology, 2025)
Kidney transplant recipients (KTRs) carry an elevated risk of cancer-related mortality. The cumulative incidence of de novo post-transplant malignancy (DPTM) reaches 10% at 10 years, with renal cell carcinoma (RCC) arising in native kidneys being the predominant urologic malignancy. This study presents three KTRs who developed native kidney RCC 6–15 years post-transplantation. Notably, Case 1 demonstrated a 14.7 cm mass at diagnosis, secondary to non-adherence to protocol-based native kidney surveillance. Histopathological confirmation of RCC was established in all cases through ISUP/WHO-graded surgical specimens and immunophenotypic profiling. KTRs exhibit elevated native kidney RCC risk, often with nonspecific clinical presentations. Our findings emphasize the critical role of systematic imaging protocols, particularly ultrasonography and contrast-enhanced ultrasound (CEUS), in early tumor detection. Implementing these strategies may improve survival and reduce disease burden in this high-risk population.